2017
DOI: 10.1089/pho.2016.4172
|View full text |Cite
|
Sign up to set email alerts
|

Low-Level Laser Therapy for Reducing the Hip, Waist, and Upper Abdomen Circumference of Individuals with Obesity

Abstract: Objective: To assess the effectiveness of low-level laser therapy (LLLT) for reducing hip, thigh, and abdomen circumference of individuals with body-mass index (BMI) between 30 and 40 kg/m 2. Background: Previous studies demonstrated the effectiveness of LLLT for reducing body circumference in the hips, thighs, and abdomen of nonobese individuals with a BMI <30 kg/m 2. Methods: In this randomized, double-blind shamcontrolled study, obese, but otherwise healthy, individuals were randomized to undergo 30-min LLL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…A second Scopus database search was undertaken to evaluate the effects of green light PBM using the terms described in Figure 3b. An initial search resulted in 236 articles being identified and these articles were subsequently screened for suitability, which then identified 32 relevant articles for further review (18,32,33,64,68,69,79,164,168,171,176,177,186,197,205,209,(212)(213)(214)(215)(216)(217)(218)(219)(220)(221)(222)(223)(224)(225)(226)(227).…”
Section: Kazemi Khoo Et Al 2013(184)mentioning
confidence: 99%
“…A second Scopus database search was undertaken to evaluate the effects of green light PBM using the terms described in Figure 3b. An initial search resulted in 236 articles being identified and these articles were subsequently screened for suitability, which then identified 32 relevant articles for further review (18,32,33,64,68,69,79,164,168,171,176,177,186,197,205,209,(212)(213)(214)(215)(216)(217)(218)(219)(220)(221)(222)(223)(224)(225)(226)(227).…”
Section: Kazemi Khoo Et Al 2013(184)mentioning
confidence: 99%
“…Other research has shown low-level laser therapy for reducing the hip, waist, and upper abdomen circumference of individuals with obesity and when applied to individuals with a BMI between 30 and 40 kg/m2 is successful 23 and may reflect the power of low level laser applications to reduce inflammatory processes associated with obesity 5,24,25 and pain. 25 It may also enhance exercise associated benefits to reduce obesity, [26][27][28][29] as well as the extent of comorbid disease associations.…”
Section: Resultsmentioning
confidence: 98%